Pengembangan Evaluasi Pembelajaran Berbantuan Wordwall Materi Melaksanakan Pengurusan Jenazah Untuk Kelas 11 SMA Negeri 12 Luwu Utara - Andika, Putri Rahmadani; Fakhrunnisaa, Nur; Nursyamsi, Nursyamsi (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The research discusses the instrument for developing learning evaluations assisted by wordwall material for carrying out corpse management for class Types of R&D (Research and Development) research, ADDIE model: Analysis (analysis), Design (design), Development (development), Implementation (implementation), Evaluation (evaluation). The subject is a class XI IPA student at SMAN 12 North Luwu. Observation data collection techniques, questionnaires and documentation. Data analysis techniques, qualitative descriptive analysis and quantitative descriptive analysis. The research results showed that media experts were 95% in the